Nutritional Strategies for Peak Performance: Guidelines for Athletes’ Optimal Fueling and Recovery - ceylan, Halil İbrahim (Health Nexus, 2023)
This narrative review aims to consolidate existing knowledge on nutritional strategies that optimize athletic performance and recovery, highlighting the significance of tailored nutritional plans for athletes. A comprehensive literature search was performed across several databases, focusing on peer-reviewed studies, reviews, and consensus statements related to sports nutrition. The review emphasizes macronutrients, micronutrients, hydration, supplementation, and the timing of intake in relation to athletic performance and recovery. The review identifies that personalized nutrition plans, which consider individual athlete needs and sport-specific demands, are crucial for enhancing performance and facilitating recovery. It also underscores the importance of hydration, balanced intake of macronutrients, and the cautious use of supplements. Nutritional strategies are fundamental to achieving peak athletic performance and optimal recovery. Future research should focus on personalized nutrition and the effects of long-term supplement use. Athletes and professionals are encouraged to adopt evidence-based nutritional practices tailored to individual needs and sport-specific requirements.